PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT DAN FINANCIAL DISTRESS TERHADAP INTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurhayadi, Willy; Aulia, Urfanul; Indriyanti, Almira Araminta; Fachri, Saeful (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to find out how the influence of independent commissioners, audit committees, financial distress, on the integrity of financial statements in mining companies listed on the Indonesia Stock Exchange in 2020-2023. This study uses primary data in the form of distributing questionnaires online to mining companies listed on the Indonesia Stock Exchange with a population of 46. The sample selection method is purposive sampling, so that a sample of 21 mining companies listed on the Indonesia Stock Exchange in 2020-2023 was obtained. The results of the independent commissioners, audit committees, financial distress, and the integrity of the financial statements showed a significant result. The results of data analysis or multiple linear regression show that simultaneously independent commissioners, audit committees and financial distress have a significant effect on the integrity of  financial statements